The effect of sustainable supply chain management and sustainability governance on sustainable performance - Khan, Mustafa Rehman (2022)
This study aimed to assess the key determinants of sustainable supply chain management (SSCM) (i.e., sustainable supplier management (SSM), sustainable operation management (SOM), and sustainable customer management (SCM) and examined their impact on sustainable performance (SP) (i.e., economic performance (ECP), social performance (SCP), and environmental performance (ENP)). Furthermore, this study investigated the mediating effect of sustainability governance (SSG) between SSCM and SP. A purposive sampling was used in this cross-sectional study through an online survey among managers of ISO 14001-certified Malaysian manufacturing organizations using an online questionnaire. Following a pilot test, an online survey was used to obtain 348 survey responses. After the data screening, only 328 responses were retained for analysis. The obtained data were analysed by employing PLS-SEM approach using SmartPLS 3.3.2 software. Results revealed that ECP (R2=0.540), SCP (R2=0.597), and ENP (R2=0.558) were directly influenced by SSCM and SSG. This study reported a significant effect of SSM on SCP (=0.319, t-value=6.129, p-value=0.000) and ENP (=0.340, t-value=7.225, p-value=0.000). However, the relationship between SSM and ECP was insignificant (=0.078, t-value=1.362, p-value=0.174). This study stated the significant effect of SOM on ECP (=0.249, t-value=3.039, p-value=0.002), SCP (=0.222, t-value=3.165, p-value=0.002) and ENP (=0.216, t-value=2.991, pvalue= 0.003). This study also indicated significant relationship between SCM and SCP (=0.352, t-value=6.637, p-value=0.000). Nevertheless, the effect of SCM on ECP (=0.126, t-value=1.903, p-value=0.058) and ENP (=0.033, t-value=0.055, pvalue= 0.544) was found as insignificant. Furthermore, results revealed that SSG partially mediated the relationship between SSM to SCP (VAF=0.2295) and ENP (VAF=0.2587) and SOM to ECP (VAF=0.2742), SCP (VAF=0.3138) and ENP (VAF=0.2340). In conclusion, sustainable supply chain management and SSG are significantly important to improve the sustainable performance of organisations. Hence, this study identifies the need for incorporating sustainable practices and SSG in manufacturing organizations that not only influence ENP and SCP but also increase ECP for the organization